The Influence of Training and Organizational Culture on Employee Performance Through Job Satisfaction as an Intervening Variable At PT XYZ in Bandung - Rayhana, Syifa; Setiawati, Trias (UNIVERSITAS PAKUAN, 2024)
The goal of this research is to examine the relationship between training, organizational culture, to employee performance at PT XYZ in Bandung via the moderating effect of job satisfaction. In this quantitative study, questionnaires were sent online using Google Forms to collect data. Using a stratified random sample technique, we selected 40 employees from a population of 40. The t-test, the F-test, simple and multiple linear regression analysis, and path analysis all play roles in the study's analysis procedure. The results showed that training had an effect on employee performance while organizational culture had no effect on performance, training had no effect on job satisfaction, while organizational culture had a positive effect on job satisfaction, job satisfaction had a positive and significant effect on employee performance, job satisfaction was not able to mediate the relationship between training and organizational culture on employee performance at PT XYZ in Bandung.